The Impact of Cost Sharing and Parental Participation on Secondary School Performance in Botswana - Mphafe, Ofentse; Miruka, Collins; Pelser, Theuns G. (South African Journal of Higher Education, 2016)
The Botswana government discontinued school fees in the 1980s as an attempt to address the endemic poverty and gravely unequal distribution of wealth in the country. The country invested vast amounts in education to achieve an impressive gains in educational access at all levels. However, the dawn of the new millennium came with the re-introduction of school fees termed cost recovery, the move which many authors across the world blame for eroding the gains achieved during the era of free education in a number of countries. This study seeks to investigate the changes that the exercise could have brought in the areas of parental participation and schools’ academic results. The researcher used a case study method for this qualitative research. Observations, documentary study and interviews were used to collect data. Both purposeful and random techniques were used to select respondents. The results in this study revealed that paying of secondary school fees cannot be used to enhance parental participation and good academic results of schools. However, it is proven that there is positive correlation between parental participation and the quality of school results.